DINAMIKA PERBERASAN DI SULAWESI TENGGARA - ZAINAL ABIDIN; IDRIS -; AMIRUDDIN SYAM (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2005)
The research aimed to know dynamics of rice related to rice system in South East Sulawesiwas done in September to Oktober 2004 in Kendari regency (Uepai, Amonggedo,Pondidaha and Abuki district). This research used survey methode involved 40 responden.The data used secundary data having the caracter of time series and primary data. Theresulth showed that wet paddy production was very fluctuantive. Their productivity wasrelated stable at 3,5 – 3,8 t/ha. Dry land paddy was wide enough used by farmer especialyin area that had poor paddy field, but wide area and its production had overtime trendwhile production increased. That productivity was still lower than national productivity of2,52 t/ha. Although main production more increase in the latest of 10 years, but thegovernment represented by Bulog still brought rice from out side South East Sulawesiespecially from South Sulawesi. Rice farming system was showed R/C > 1 value. Than,exchange value of benefict on cost, the use of cost was still dominated by labour. Thebenefict used for labour was 29 %. Rice farming system contributed around 75 % of totalhousehould income, besides that, farmer also obtained income from the other farmingsystem, livestock and off-farm.